The CSR-Crowdfunding Model for Strengthening the Competitiveness of SMEs and Enhancing Business Value: Model CSR-Crowdfunding Upaya Penguatan Daya Saing Ekonomi UMKM dan Peningkatan Nilai Usaha - Meliza, Juli; Zuhri, Zuhri (Indonesian Journal of Law and Economics Review, 2023)
The pattern of developing CSR as a partnership program can be done in various ways, such as community development, capacity building, product promotion, capital strengthening, etc. The urgency of this research is that CSR is one of the partnership solutions that can strengthen the competitiveness of MSMEs and increase corporate value, to open wider access to credit for the MSME actor segment which is still constrained in meeting investment and working capital needs. This research discusses the adoption of CSR principles in the crowdfunding platform, so it needs to be encouraged for small business units in the surrounding community. The purpose of this research is to analyze the relationship between crowdfunding and CSR principles, can increase the economic competitiveness of SMEs and increase corporate value. This is done to answer the challenges faced by MSMEs in accessing investment financing or working capital, which is complemented by a crowdfunding scheme that can support the financing needs of MSMEs. Highlights: CSR and crowdfunding offer partnership solutions for MSMEs' financial needs. The research aims to analyze the impact of crowdfunding and CSR on MSMEs' economic competitiveness. The study addresses challenges in MSMEs' access to investment financing and working capital through crowdfunding and CSR principles. Keywords: CSR, Crowdfunding, MSMEs, Economic Competitiveness, Corporate Value.